Clinical Usefulness of Loudness Dependence of Auditory Evoked Potentials (LDAEP) in Patients with Bipolar Disorder - Park, Young-Min (Korean Neuropsychiatric Association, 2013)
While it has been reported previously that the loudness dependence of auditory evoked potentials (LDAEP) is a putative biological marker or a predictor of treatment response, there have been few studies of LDAEP in bipolar disorder. However, a recent study by Park and colleagues raised the possibility that the LDAEP could be useful as a biological marker of bipolar disorder. They found that the LDAEP was significantly higher in normal controls than in patients with either bipolar disorder or schizophrenia. Lee and colleagues also examined the LDAEP in bipolar disorder and normal controls, and found that it differed according to the bipolar phase, being significantly higher in cases of euthymic bipolar disorder, bipolar depression, and bipolar mania. With regard to treatment response, early clinical findings were that a higher LDAEP and a stronger intensity dependence of visual evoked potentials were related to a favorable response to lithium treatment. Juckel and colleagues recently demonstrated that the pretreatment LDAEP could be a predictor of successful prophylactic lithium treatment. The present article reviews the literature in order to determine whether the LDAEP can be used as a biological marker or a predictor of treatment response in patients with bipolar disorder and of manic switch or treatment resistance in patients with major depressive episode(s).